2019
DOI: 10.1242/jeb.191593
|View full text |Cite
|
Sign up to set email alerts
|

Dissecting cause from consequence: a systematic approach to thermal limits

Abstract: Thermal limits mark the boundaries of ectotherm performance, and are increasingly appreciated as strong correlates and possible determinants of animal distribution patterns. The mechanisms setting the thermal limits of ectothermic animals are under active study and rigorous debate as we try to reconcile new observations in the lab and field with the knowledge gained from a long history of research on thermal adaptation. Here, I provide a perspective on our divided understanding of the mechanisms setting therma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
51
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 62 publications
(51 citation statements)
references
References 85 publications
0
51
0
Order By: Relevance
“…The OCLTT remains contentious; however, as for some species, temperatures that maximize aerobic scope have little relevance to real-world performance or temperature preference ( Fry, 1947 ; Clark et al , 2013 ; Norin et al , 2014 ; Jutfelt et al , 2018 ). The hypothesis predicts different mechanisms of oxygen limitation at low versus high temperatures ( Verberk et al , 2016 ; MacMillan, 2019 ) and thus could have predictive power at either temperature extreme even if not relevant at temperature optima or the other extreme. For example, energy allocation modelling of cod ( Gadus morhua ) based on the OCLTT predicts that fitness is optimized at a considerably lower temperature than aerobic scope, yet at temperature extremes, aerobic scope budgeting conflicts limit performance ( Holt and Jørgensen, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The OCLTT remains contentious; however, as for some species, temperatures that maximize aerobic scope have little relevance to real-world performance or temperature preference ( Fry, 1947 ; Clark et al , 2013 ; Norin et al , 2014 ; Jutfelt et al , 2018 ). The hypothesis predicts different mechanisms of oxygen limitation at low versus high temperatures ( Verberk et al , 2016 ; MacMillan, 2019 ) and thus could have predictive power at either temperature extreme even if not relevant at temperature optima or the other extreme. For example, energy allocation modelling of cod ( Gadus morhua ) based on the OCLTT predicts that fitness is optimized at a considerably lower temperature than aerobic scope, yet at temperature extremes, aerobic scope budgeting conflicts limit performance ( Holt and Jørgensen, 2015 ).…”
Section: Introductionmentioning
confidence: 99%
“…The OCLTT has scarcely been tested at long-term, sub-lethal temperatures ( Verberk , et al , 2016 ) or under naturally varying conditions ( Morash et al , 2018 ) relevant to range extensions. Thus, tests of this framework in the context of species’ range extensions are important because if the OCLTT has limited power to predict species’ cold range limits, research effort can be more fruitfully allocated towards other potential mechanisms ( Clark et al , 2013 ; Sinclair et al , 2016 ; MacMillan, 2019 ).…”
Section: Introductionmentioning
confidence: 99%
“…2) injury to the integrating neural centers, 3) loss of function in the neuromuscular excitationcontraction coupling (not investigated here), or 4) a combination of all three (1, 45).Cold-induced cell death in insect muscle is thought to be the consequence of a debilitating cascade, at the centre of which is a loss of ionoregulatory capacity that drives hemolymph hyperkalemia. This hyperkalemia, in turn, depolarizes muscle tissue and induces an excessive Ca 2+ influx, increasing the intracellular [Ca 2+ ], and this is thought to activate apoptotic/necrotic pathways and thereby drive injury phenotypes (1,18,[21][22][23]45). In our experiments we found that exposure to both prolonged cold and lethal heat (positive control) induced a marked increase in caspase-3-like activity in muscle tissue(Fig.…”
mentioning
confidence: 59%
“…1A), despite being more tolerant of chilling by every other measure. The CCO, CCRT, and chilling injury are all thought to be related to the capacity to maintain ion and water balance, but are mediated by different specific physiological mechanisms of failure occurring in different organs and across different time scales (MacMillan, 2019; Overgaard & MacMillan, 2017; Robertson et al, 2017). Our results in the present study thus suggest that acclimation alters mechanisms underlying CCRT and the development of chilling injury without impacting the temperature that causes paralysis.…”
Section: Discussionmentioning
confidence: 99%
“…While tolerance to extreme cold relies on a physiological capacity to avoid or survive ice formation inside the body, tolerance to chilling requires a physiological capacity to resist the effects of low temperature per se on organ, tissue, and cellular biochemistry (MacMillan, 2019; Overgaard & MacMillan, 2017; Teets & Denlinger, 2013). Consequently, measures of cold tolerance relevant to freeze avoidant and freeze tolerant insects, such as the supercooling point (the temperature of spontaneous ice formation within the body) or survival following freezing, are irrelevant to characterizing the thermal limits of chill susceptible insects (Overgaard & MacMillan, 2017).…”
Section: Introductionmentioning
confidence: 99%